La cuestión del mal desde el pensamiento de Schopenhauer - Andrade Alarcón, Luis (Archivos de criminología, seguridad privada y criminalística, 2020)
The exercise of Philosophy has been necessary for the consolidation of knowledge, and as far as Criminology is concerned, it serves to unveil the most disturbing problems in the world, crime. From the hand of the German philosopher Arthur Schopenhauer, we will understand the condition of man.